2023
DOI: 10.1038/s41598-023-34072-4
|View full text |Cite
|
Sign up to set email alerts
|

Screening marker genes of type 2 diabetes mellitus in mouse lacrimal gland by LASSO regression

Abstract: Type 2 diabetes mellitus (T2DM) is characterized by insulin resistance and a relative deficiency of insulin. This study aims to screen T2DM-related maker genes in the mouse extraorbital lacrimal gland (ELG) by LASSO regression.C57BLKS/J strain with leptin db/db homozygous mice (T2DM, n = 20) and wild-type mice (WT, n = 20) were used to collect data. The ELGs were collected for RNA sequencing. LASSO regression was conducted to screen marker genes with the training set. Five genes were selected from 689 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Zhang et al identified key modules and hub genes involved in the pathogenesis of OSCC by applying WGCNA to construct a gene co-expression network for the first time, and their study is of great significance for exploring the mechanism of OSCC tumourigenesis and searching for new prognostic biomarkers and therapeutic targets [ 35 ]. Compared with previous studies, the integrated procedure used in this study has the distinct advantage of selecting common markers shared by the combination of the three algorithms [ 28 , 29 ], thus reducing the number of markers while significantly improving the specificity and sensitivity of the identification indicators. Notably, SEMA3C emerged as the most significant hub gene through this comprehensive approach, and the diagnostic efficacy of elevated SEMA3C in distinguishing individuals with TSCC from those without was evaluated using ROC analysis, which yielded high-accuracy results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al identified key modules and hub genes involved in the pathogenesis of OSCC by applying WGCNA to construct a gene co-expression network for the first time, and their study is of great significance for exploring the mechanism of OSCC tumourigenesis and searching for new prognostic biomarkers and therapeutic targets [ 35 ]. Compared with previous studies, the integrated procedure used in this study has the distinct advantage of selecting common markers shared by the combination of the three algorithms [ 28 , 29 ], thus reducing the number of markers while significantly improving the specificity and sensitivity of the identification indicators. Notably, SEMA3C emerged as the most significant hub gene through this comprehensive approach, and the diagnostic efficacy of elevated SEMA3C in distinguishing individuals with TSCC from those without was evaluated using ROC analysis, which yielded high-accuracy results.…”
Section: Discussionmentioning
confidence: 99%
“…It can greatly narrow down the range of genes to be screened, thereby increasing the accuracy of pinpointing genes associated with key traits [ 28 ]. LASSO regression is based on the regression method, which reduces the complexity of the model, prevents overfitting, and utilizes a smaller sample size to effectively filter features, resulting in a more accurate prediction algorithm [ 29 ]. RF algorithms are more accurate and well-suited for analyzing complex data, such as omics data, which is often high-dimensional [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
“…(2) The merging genes found in the PPI network and these RF-screened significant genes intersected, and the resulting genes were chosen as candidate modeling genes. (3) Using the R “glmnet” packages, the least absolute shrinkage and selection operator (LASSO) logistic regression ( 27 ) was used to further reduce the range of potential modeling genes. Ultimately, the hub MitoDEGs in AD were chosen using ten-fold cross-validation to determine the optimum λ and the risk score for each sample was computed using the method that follows:…”
Section: Methodsmentioning
confidence: 99%
“…These regression models have been used for studies where the number of input variables are large relative to the sample size. 42,43 PLS regression has been used for datasets with mutually correlated input variables and output variable, and important predictors can be estimated by VIP. 31 Here, high VIP indicates high contribution of the variables in predicting DI.…”
Section: Predicting DI From Cgm Single-point Blood Tests and Physical...mentioning
confidence: 99%